Flipped out in the blended classroom, the good, the bad and the ugly: When academics become students - van den Berg, C.L.; Verster, B.; Collett, K.S. (South African Journal of Higher Education, 2018)
This paper explores the well-being of three academics from different higher education institutions and disciplines, as they engage in professional academic development (PAD) courses using technology. A collaborative autoethnographic approach is applied to reflect on our professional development experience. The higher education landscape is shifting to a cloud-based ICT infrastructure, opening up multiple educational opportunities in teaching and learning. Lecturers in higher education institutions (HEIs) are required to use a range of new technological tools and applications and engage in new learning methodologies. This is modelled in professional academic development courses, which integrate technology and digital tools into the teaching and learning process. Participant perspectives on PAD within a blended learning environment are examined through the lenses of an ethic of care and authentic learning to uncover social justice pedagogy. Using a diffractive approach in a collaborative autoethnographic study, the possibilities, tensions and contradictions of using technology to enhance pedagogy are explored. Findings point to the importance of an Ethic of Care and authentic learning, in order to enhance a social justice pedagogy in PAD.